Metabolic response of fresh-cut apples induced by pulsed electric fields. (December 2016) - Dellarosa, Nicolò; Tappi, Silvia; Ragni, Luigi; Laghi, Luca; Rocculi, Pietro; Dalla Rosa, Marco
Abstract: Pulsed electric field (PEF) treatments can induce metabolic stress responses in plant tissue as a function of the applied conditions. This study highlighted the metabolic effects of reversible and irreversible electroporation in fresh-cut apple tissue, by adjusting the electric field strength to 100, 250 and 400 V/cm (100 μs pulse width, 60 pulses, 100 Hz). Metabolic heat, O2 and CO2 gas analysis, along with metabolomics, were employed to jointly evaluate the PEF-induced effects after 24 h at 10 °C. Marked metabolic changes were registered when the threshold of irreversible electroporation was exceeded, at 250 and 400 V/cm. With such treatments, a drop of metabolic heat and respiration rate was observed, as a probable consequence of the loss of the cell viability, anaerobic respiration pathways were noticeably lowered, while γ-aminobutyric acid metabolism was activated. Conversely, minimal modifications of the metabolism heat and metabolites concentrations were noticed when 100 V/cm was applied. Industrial relevance: Metabolic response of fresh-cut fruit and vegetables as function of the manufacturing process is a fundamental aspect directly related to the quality of the final products. Pulsed electric fields (PEF), as well as other innovative technologies, can induce undesired effects on tissue metabolism that might limit the industrial application. Furthermore, the analytical methods used in the present work provide useful tools for the optimization of the PEF treatment conditions for fresh-cut manufacturers. Highlights: PEF effects on fresh-cut apple metabolism within 24 h at 10 °C were evaluated. Calorimetry and metabolomics finely described the PEF-induced metabolic response. Metabolic heat and respiration dropped when irreversible electroporation took place. GABA and anaerobic metabolic pathways were altered by pulsed electric fields.